One Way Traffic: Base‐to‐Backbone Hole Transfer in Nucleoside Phosphorodithioate. Issue 43 (22nd June 2020) - Kaczmarek, Renata; Ward, Samuel; Debnath, Dipra; Jacobs, Taisiya; Stark, Alexander D.; Korczyński, Dariusz; Kumar, Anil; Sevilla, Michael D.; Denisov, Sergey A.; Shcherbakov, Viacheslav; Pernot, Pascal; Mostafavi, Mehran; et al.
Abstract: Invited for the cover of this issue are the groups of Roman Dembinski, Mehran Mostafavi, and Amitava Adhikary at the Polish Academy of Sciences, Université Paris‐Saclay, and Oakland University. The image depicts a doughnut as a way of illustrating the hole transfer process. Read the full text of the article at 10.1002/chem.202000247 . Abstract : " Direction of this hole transfer process reverses (i.e., base‐to‐backbone) if hole transfer occurs when two oxygen atoms in the phosphate group are substituted by two sulfur atoms (phosphorodithioate). This could be the key step in the mechanism of the phosphorodithioate‐induced toxicity in humans ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 9495 ff. (DOI: 10.1002/chem.202000247 ).